Estimating the Material Stock of Roads: The Vietnamese Case Study. (10th July 2018) - Nguyen, Thi Cuc; Fishman, Tomer; Miatto, Alessio; Tanikawa, Hiroki
Summary: This study is a pioneering effort to quantify the materials stocked in the road network of a developing country, Vietnam, and analyze its relationships to the country's recent economic development. National road networks function as capital and infrastructure investments that are necessary catalysts for countries' development, while requiring the extraction of vast amounts of construction materials for expansion and maintenance causing environmental impacts. However, there has so far been little research on the subject, especially in developing countries. We compile material stock and flow accounts for Vietnam's roads from 2003 to 2013 on the national and provincial levels, finding that approximately 40% of the domestic consumption of construction materials is for expanding and maintaining the road network, and the materials stocked in the road network doubled from 1, 321 million metric tons in 2003 to 2, 660 million metric tons in 2012. Material stock growth rates closely resembled those of gross domestic product (GDP) in this period, suggesting a codependency of physical infrastructure development and economic development. On the provincial level, our results show local disparities in the stock and its capacity to support the transportation of passengers and freight, especially considering the surging growth of vehicles in urban centers. By showcasing the challenges of conducting a material flow and stock analysis in a developing country, this study not only sheds light on Vietnam's transportation material stock and its policy implications, but also serves as a case study for further work in similar countries.